The Sistah Powah Structured Writing Intervention: A Feasibility Study for Aging, Low-Income, HIV-Positive Black Women. Issue 2 (November 2013) - DeMarco, Rosanna F.; Chan, Keith
Purpose: The purpose of this study was to test the feasibility and assess outcomes of health care adherence based on whether participants engage in particular risky behaviors relevant to general health or living with human immunodeficiency virus (HIV) infection and the frequency of these adherent behaviors. Health adherent behaviors include both self-advocacy and decreased stigma as underlying key components. Design: A randomized control trial comparing peer-led attention control support and intervention groups. Setting: Community-based women's drop-in center in an urban, black neighborhood of Boston, Massachusetts. Subjects: Aging, low-income, black women living with HIV infection. Intervention: Peer-led, small-group, structured writing using film clips from Women's Voices Women's Lives as a writing prompt. Measures: Demographic and outcome data that included adherence, self-advocacy, and stigma; collected at baseline, 6 weeks, and 6 months. Analysis: Repeated-measures analysis of variance scores were examined between groups and waves. Paired-sample t-tests were used to examine mean differences across time. Results: Sample included 110 women (intervention, n = 56; comparison, n = 54). Retention was 85.5%. Repeated-measures analysis indicated intervention group condom use (n = 69, F = 8.02, df = 1, p < .01) and safe sex (n = 71, F = 13.02, df = 1, p < .01) was higher than that of comparison group. A time effect was also found in the Silencing the Self Scale (n = 91, Pillai's trace = 7.21, df = 2, p < .01). Conclusion: This study demonstrates the feasibility of a tailored, peer-led, and culturally relevant interventions and tentative efficacy in populations affected by health disparities. Key limitations include no comparison intervention format with women who can't write and the need to test generalizability.